2004
DOI: 10.1523/jneurosci.1197-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Regulates the Onset and Severity of Motor Dysfunction Associated with Enkephalinergic Neuronal Degeneration in Huntington's Disease

Abstract: The mechanism that controls the selective vulnerability of striatal neurons in Huntington's disease is unclear. Brain-derived neurotrophic factor (BDNF) protects striatal neurons and is regulated by Huntingtin through the interaction with the neuron-restrictive silencer factor. Here, we demonstrate that the downregulation of BDNF by mutant Huntingtin depends on the length and levels of expression of the CAG repeats in cell cultures. To analyze the functional effects of these changes in BDNF in Huntington's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
294
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(314 citation statements)
references
References 50 publications
15
294
0
Order By: Relevance
“…Given these promising results, it would be interesting to evaluate the effects of AdBDNF/AdNoggin treatment on the striatal neuropathology of R6/2 mice. Indeed, the importance of BDNF in HD neurodegeneration was previously demonstrated by disrupting the expression of the bdnf gene in R6/1 mice (Canals et al, 2004). Decreased levels of this neurotrophin were shown to advance the onset of motor dysfunction and cause the specific degeneration of enkephalinergic striatal projection neurons (the most affected neurons in HD).…”
Section: Therapies Aimed To Restore Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Given these promising results, it would be interesting to evaluate the effects of AdBDNF/AdNoggin treatment on the striatal neuropathology of R6/2 mice. Indeed, the importance of BDNF in HD neurodegeneration was previously demonstrated by disrupting the expression of the bdnf gene in R6/1 mice (Canals et al, 2004). Decreased levels of this neurotrophin were shown to advance the onset of motor dysfunction and cause the specific degeneration of enkephalinergic striatal projection neurons (the most affected neurons in HD).…”
Section: Therapies Aimed To Restore Neurogenesismentioning
confidence: 99%
“…Decreased levels of this neurotrophin were shown to advance the onset of motor dysfunction and cause the specific degeneration of enkephalinergic striatal projection neurons (the most affected neurons in HD). Importantly, this neuronal dysfunction was restored by administration of exogenous BDNF, suggesting that this neurotrophic factor might help delaying or stopping illness progression (Canals et al, 2004). More recently, CEP-1347, a mixed lineage kinase inhibitor with neuroprotective and neurotrophic effects, was shown to restore the expression of BDNF Conforti et al, 2008) and improve motor performance in R6/2 mice .…”
Section: Therapies Aimed To Restore Neurogenesismentioning
confidence: 99%
“…We previously demonstrated that htt also participates in post-Golgi trafficking of proteins that follow the regulated secretory pathway (del Toro et al, 2006). Thus, mutant htt (mhtt) impairs post-Golgi trafficking, which in turn decreases the number of vesicles containing BDNF, thereby contributing to a reduced trophic support that is essential for striatal neurons during HD progression (Canals et al, 2004). However, the molecular mechanism by which htt participates in post-Golgi trafficking remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) plays a critical role in the pathophysiology of different neurodegenerative diseases, such as Huntington's disease (HD) (Zuccato et al, 2001;Canals et al, 2004). HD is a neurodegenerative disorder caused by a multiple CAG expansion in exon1 of huntingtin (htt) gene (Kremer et al, 1994), producing a significant dysfunction and neural death, especially in the medium spiny neurons of the striatum.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to BDNF, htt enhances the transcription of BDNF by the inhibition of the neuron restrictive silencer element (Zuccato et al, 2003) and promotes the transport of BDNF-containing vesicles along microtubules (Gauthier et al, 2004). Thus, the mutation of htt produces a reduction in BDNF expression (Ferrer et al, 2000;Zuccato et al, 2001) and release (Gauthier et al, 2004), which in turn affect the survival action of BDNF on striatal neurons (Canals et al, 2004).…”
Section: Introductionmentioning
confidence: 99%